(untitled) (Physical Education, Health and Social Sciences, 2024)
Engaging in fitness for health benefits is advantageous. It is the quality that enables an individual to perform daily tasks effectively and efficiently. Flexibility is a component of health-related fitness. The principal objective of the present study was to evaluate the impact of aerobic training and hatha yoga on the flexibility of the lower back, shoulders, and core back in overweight college students. Two groups each of twenty-five volunteers, aged 20 to 24, were selected for the study using the PAR-Q. Pre-test data on dependent variables was collected using the sit-and-reach test, back extension, and shoulder elevation. The participants in the hatha group and the aerobic group engaged in 10 weeks of Hatha yoga and aerobic exercise, respectively, three days per weeks. Subsequent to the intervention, post-test data on dependent variables were collected utilising the identical methods employed for pre-test data collection. The pre- and post-collection data for each group’s subjects were compiled. The data were examined utilizing the following statistical tests: independent samples t-test, paired samples t-test, and mean calculation. A constant significance level of 0.05 was utilized. The flexibility of the shoulder, lower back, and core back is considerably influenced by both training regimens. Moreover, among overweight college students aged 20 to 24, yoga exercises had superior effects on shoulder flexibility, core back flexibility, and lower back flexibility compared to aerobic training. Students with excess weight are encouraged to participate in aerobic and hatha yoga exercises to enhance their overall fitness levels. Keywords- Hatha Yoga, Aerobic training, Flexibility, Shoulder, Core back, lower back, Overweight College Students